Implementasi Program Jari Tangan: Analisis Pelaksanaan dan Dampaknya - Isyfi Syaufi Nafilah; Wazirul Luthfi; Winar Nur Aisyah Fatimah; Slamet Achrodi; Diaz Alvin Firdausa; Annisa Nur Fadhlillah (Syntax Corporation Indonesia, 2023)
The popularity of Corporate Social Responsibility (CSR) continues to rise, reflecting a company's commitment to addressing social and environmental issues to support sustainable development. As an example of CSR commitment, PT Pertamina EP Zona 7 Jatibarang Field has put this approach into practice. Their community development program, known as